Crossing Japanese Rice Products with Italian Futurism: Fortune Cookies, Onigiri and Arancini as Communicant Rice-Bites - Condello, Annette (Routledge, 2019)
This chapter unravels the intertwined influences of the rice traffic between Japanese culture and Italian futurism. Interpreting the way Japanese cuisine was understood in the Italian context, it explains how Italian cuisine became established in Japan. As “communicant” rice-bites, fortune cookies, onigiri and arancini impart Futurist messages through their spherical form. “Rice oranges” appealed to Futurist protagonist Filippo Tommaso Marinetti, celebrated author of The Futurist Cookbook (1932). This chapter demonstrates why the Italian Futurists were attracted to Japanese cuisine through its military dimension. Analyzing the cookbook’s Japanese origins and Marinetti’s penchant for fast, portable tidbits, the chapter argues how some recipes, consumed in foil-like interiors, were indebted to Asian traditions.